Clinical Spectrum of XDR and MDR Enteric Fever in Children Aged Between 6 Months to 15 Years at The Children’s Hospital, Lahore - Khan, Muhammad Zeeshan; Ashraf, Samreen; Javed, Humera; Zafar, Aizza; Khan, Fariha Ahmad; Rashid, Junaid (Infectious Diseases Journal of Pakistan, 2022)
Background: To determine the clinical spectrum of XDR and MDR enteric fever in children. Methods: A cross sectional study conducted at pediatric medical units of the Children’s Hospital and the Institute of Child Health, Lahore from May 2019 to Feb 2020. 135 children of both genders between 6 months to 15 years of age fulfilling the operational definition of enteric fever were included in the study. All study cases were evaluated for clinical features, possible complications, antimicrobial sensitivity pattern and duration of stay in the hospital. Data was analyzed by using SPSS version 23. Results: Mean age of our study cases was 6 years with male preponderance (69.6%). Majority (44.4%, n=60) were between 1 to 5 years of age out of which significant number of children (20%) were between 6 months to 2 years. Among patients between 6 months to 2 years, 67.8% ( n=19) were XDR. Fever was present in 100% followed by GI symptoms (40%) including nausea, vomiting, diarrhea and abdominal pain. Among all bacterial isolates of enteric fever, 54.1% were XDR, 20% were extended spectrum beta lactamase positive (ESBL), 18.5% were MDR and 7.4% were non-resistant. Levofloxacin was found to be sensitive in 41% of the total cases as compared to ceftriaxone (23%) and ciprofloxacin (22%). 8.8% of cases developed complications majority of them were XDR Enteric. Hepatobiliary complications (splenic infarcts, icteric hepatitis, pancreatitis) were found in 5.1 %, followed by CNS complications (cerebellar ataxia, meningitis (2.2%). XDR enteric was significantly associated with male gender (p-value 0.025), prolonged durations of fever (p-value 0.047) and hospital stay (p-value 0.010). Conclusion: XDR enteric fever constitutes more than 50% of total enteric fever cases with prolonged hospital stay and chance of complications as compared to MDR enteric fever. Key words: Enteric fever, XDR, MDR, ESBL, Levofloxacin, Children